Short report: 4-Aminopyridine—a new drug tested in the treatment of Eaton-Lambert syndrome - Lundh, H. (1977)
A 67 year old man with the myasthenic syndrome associated with small cell bronchogenic carcinoma was treated with a new drug, 4-aminopyridine. The muscle weakness showed marked improvement and electrophysiological examinations demonstrated restoration of neuromuscular transmission.